The development of critical thinking in grade 11 biology students through problem-based learning with forensic science issues - Meesamran, Nontawat; Polyiem, Titiworada (Journal of Green Learning, 2024)
Critical thinking is crucial for biology education and requires an instructional method that allow learners to acquire the skill through hand-on experiences with content related to learners’ lives. This action research aimed to enhance the critical thinking skills of Grade 11 students using problem-based learning (PBL) integrated with forensic science issues in a biology course on the circulatory system. The study was developed in an action research design. The study involved 12 students from a public school in the Thai educational context. The research instruments included a PBL learning management plan, a critical thinking assessment, and an interview form. Data analysis showed that in the first cycle, the average critical thinking score was 67.08%, with 58.33% of students meeting the 70% threshold. After revising the learning activities, the second cycle showed an average score increase to 83.75%, with all students surpassing the 70% threshold. These findings contribute to the research area by demonstrating the effectiveness of integrating PBL with forensic science to enhance critical thinking skills in biology education. The implementation of PBL with forensic science issues should be more investigated in other topics.